Pengaruh Tingkat Pendidikan Dan Jenis Pekerjaan Orang Tua Terhadap Prestasi Belajar Pada Mata Pelajaran Pkn Siswa Kelas II Sd Muhammadiyah 4 Kandangsapi Tahun 2015/2016 - SUBEKTI, INDAH TRI, Drs. Saring Marsudi, SH. M.Pd (2016)
The family environment and the school environment plays an important role in achieving a feat. This study aims to determine: (1) the effect of parental education on learning achievement in the subjects Civics grade II SD Muhammadiyah 4 Kandangsapi, (2) the influence of the work of parents to the student achievement in the subjects Civics second grade students of SD Muhammadiyah 4 Kandangsapi, (3) the effect of educational level and occupation of parents of students learning achievement Civics class II SD Muhammadiyah 4 Kandangsapi. This type of research is quantitative research. Data collection techniques used were documentation and interviews. Techniques digunkan prerequisite test is a test of normality and linearity. The analysis technique used is multiple regression analysis, t-test, f, and look for the amount of donations given. From the calculation results obtained ttable> t table (3.240> 2.048) and ρ-value <0.05 (0.003 <0.05). From the calculation results obtained ttable> t table (2.323> 2.048) and ρ-value <0.05 (0.028 <0.05). From the calculations, the F count> F table (27.015> 3.32) and ρ-value <0.05 (0.000 <0.05). From the calculation of regression coefficients of parental education level of 1.369 is greater than the value of the regression coefficient kind of work the parents of 0,836. So that the conclusions of this study are (1) the level of education and occupation of parents has a significant influence on learning achievement Civics grade II SD Muhammadiyah 4 Kandangsapi, (2) the level of parental education affects more dominant than the kind of work the parents to the student achievement Civics grade II SD Muhammadiyah 4 Kandangsapi.